2016
DOI: 10.1016/j.ijpsycho.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Best method for analysis of brain oscillations in healthy subjects and neuropsychiatric diseases

Abstract: The research related to brain oscillations and their connectivity is in a new take-off trend including the applications in neuropsychiatric diseases. What is the best strategy to learn about functional correlation of oscillations? In this report, we emphasize combined application of several analytical methods as power spectra, adaptive filtering of Event Related Potentials, inter-trial coherence and spatial coherence. These combined analysis procedure gives the most profound approach to understanding of EEG re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 114 publications
0
18
0
1
Order By: Relevance
“…In this study, spontaneous resting state EEG, sensory ERP and selective-attention ERP were used as three methods to obtain the important brain oscillations (Başar et al, 2016). Both EEG and ERP variables have been investigated as potential biomarkers to detect MCI and its progression to AD dementia, as well as to directly detect AD dementia (Herrmann and Demiralp, 2005;Uhlhaas and Singer, 2006;Jackson and Snyder, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, spontaneous resting state EEG, sensory ERP and selective-attention ERP were used as three methods to obtain the important brain oscillations (Başar et al, 2016). Both EEG and ERP variables have been investigated as potential biomarkers to detect MCI and its progression to AD dementia, as well as to directly detect AD dementia (Herrmann and Demiralp, 2005;Uhlhaas and Singer, 2006;Jackson and Snyder, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Oscillatory activity of neural populations has been suggested to represent a major communication mechanism of the brain (Buzsáki et al, 2013 ) and has furthermore been related to cognitive functions (Basar et al, 1999 ; Herrmann and Knight, 2001 ). Consequently, abnormal oscillatory activity has been associated with psychiatric and psychological disorders such as ADHD, Alzheimer’s disease, schizophrenia, bipolar disorder, or mild cognitive impairment (e.g., Başar, 2013 ; Başar and Güntekin, 2008 ; Başar et al, 2016 ). Electrophysiological studies of the normal functioning of basal ganglia-thalamocortical circuits and the pathophysiology of Parkinson’s disease provided insights into the functional role of neural oscillations (Schnitzler and Gross, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Of note, the behavior of local and long-range synchronized neural activities at different frequency bands have shed a spotlight on both healthy cognition and pathophysiological underpinnings of psychiatric diseases. 10,11 From another point of view, most of the existing brain neuroimaging studies reported neurological abnormalities of mood disorders at the group level with limited clinical translational value at the individual subject level. For this reason, advanced machine learning methods, which allow individual prediction, are increasingly used in the neuroimaging community.…”
mentioning
confidence: 99%
“…First, we aimed to characterize the spectral fingerprint discriminations of the MEG data during the resting-state between BD, UD, and HC. Spectral fingerprints are divided into the following classical frequency bands: delta band (1-4 Hz), theta band (4-8 Hz), alpha band (8)(9)(10)(11)(12)(13)(14), beta band (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma band . The second goal was to build a machine learning model to automatically distinguish BD, UD, and HC based on MEG resting-state brain activities.…”
mentioning
confidence: 99%